Formulasi dan Evaluasi Parfum Tipe Eau de Toilette (EDT) “Senarai Jingga” - Indra Gunawan; Pudji Rahayu (Jurnal Kesehatan, 2021)
Lack of research on formulation and evaluation of fragrance products (perfumes) in Indonesia and the need to improve the publication and branding of Tanjungkarang Health Polytechnic (Polkestanka) can be done through the development of perfume products according to climate characteristics in Indonesia. This research with quantitative experimental design aims to produce formulas and fragrance products (perfumes) type Eau de Toilette (EDT) that has the equivalent or better quality of branded perfumes on the markets. The Intervention has done by formulating perfume "Orange List" type EDT with 5 (five) series of fragrance ingredients 6-10% by Indonesian National Standard (SNI) 16-4949-1998 then compare it with positive control. The research was conducted from April 2020 until September 2020 at the Laboratory of Pharmaceutical Department of Polkestanka Pharmacy. The results organoleptically showed the entire formula produces 100% clarity, homogeneous 100%, particle-free 100%, and citrus smell. The density of all formulas meets the requirements, with the density largest in F5 of 0,86. The fragrance resistance test of the entire formula still smelled at the 4th hour and with the spot largest test result in F2 with a diameter of 75,59 mm.  The most preferred "Senarai Jingga" formula is F5 (60%). Kendall's W Test analysis obtained a significance of 0,016 that showed respondents preferred "Senarai Jingga" Perfume over positive control by the alignment of respondents judging the two perfumes to be significantly different. The later research suggests is that a favorite level test between “Senarai Jingga" Perfume and different positive controls (other brand perfumes) with citrus characteristics is required.